AN ADULT WITH MYOCARDIAL INFARCTION AND KAWASAKI DISEASE - A. A. Vostokova; E. A. Grunina; A. V. Klemenov (Российский кардиологический журнал, 2015)
Kawasaki disease — an acute systemic vasculitis with often involvement of coronary arteries — develops almost only in children. The most serious signs of Kawasaki disease are coronaritis and coronary arteries aneurisms. Aneurism thrombosis is possible complication of the disease and potential cause of myocardial infarction in youths. The case study presented of Kawasaki disease, complicated by myocardial infarction development in adult patient.